PERCEPTION OF MUHAMMADIYAH UNIVERSITY SOCIAL HUMANITIES LECTURER PROF. DR. HAMKA ON ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Prima Gusti Yanti; Ummul Qura; Nini Ibrahim (Universitas Indraprasta PGRI, 2020)
Abstract: This study aims to collect data and describe the perceptions of the lecturers of socialhumanities Prof. DR. HAMKA (UHAMKA) about the online learning process that took placeduring the Covid-19 pandemic. This is very important to know because the future withtechnological advances in the industrial era 4.0 learning like this must be faced. The method usedin this research is descriptive qualitative. The approach of this qualitative method is a case studywith a questionnaire instrument. The data analysis technique in this case study was carried out byentering data from Google Forms into Microsoft Excel. The results showed that there were stilllecturers who stated that they had encountered obstacles in implementing online learning behindthe many lecturers who were ready to face virtual learning situations during the pandemic. Then,the perceptions of social humanities lecturers on the learning process show that the perception ofpedagogic competence is at a score of 66 (sufficient), the perception of personality competence isat a score of 77 (good), the perception of social competence is at a score of 74 (sufficient), and theperception of professional competence is at a score of 78 (good).Key Words: Persepsi, PJJ, Dosen, Pandemi Covid-19